Pattern of utilization of pharmacy value-added services in 2019 and 2020 at health facilities in Selangor, Malaysia - Josephine Henry Basil, Chong Pei Feng, Asmahani Ramelan, Dzafarullah Daud, Hazlinda Nazli Naem, Kong Su Shan, Lau Siew Yan, Mohd Dziehan Mustapa, Nur Kamalah Daud, Rozian Abu Chik, Ruwaida Nur Zainol Abidin, Shahir Anuar Shahrani, Teh Chew Charn, Mohd Shahezwan Abd Wahab,, Nur Wahida Zulkifli (Journal of Applied Pharmaceutical Science, 2022)
Pharmacy value-added services (PVAS) include any innovative pharmacy activities to facilitate and aid the refilling of medications. In Malaysia, the government has invested in infrastructure development, promotional activities, and manpower to enhance PVAS utilization. In this study, PVAS data for the years 2019 and 2020 that were obtained from all public health facilities in the state of Selangor, Malaysia, were analyzed to identify the pattern of PVAS utilization. A reduction in the total number of new and refill prescriptions was observed in 2020. The number of patients enrolled in a PVAS program increased by 44.5% in 2020. Overall, totals of 222,358 and 416,635 prescriptions were supplied through the PVAS programs in 2019 and 2020, respectively. The most common PVAS that was newly offered in 2020 was the medicines by post (locally known as Ubat Melalui Pos) service. The service was also the most utilized PVAS by patients in 2020. The average waiting time per prescription for patients receiving their medications from the outpatient pharmacies at the hospitals increased slightly in 2020 but was reduced at the health clinics. Activities such as campaigns to promote PVAS can be undertaken to further enhance the utilization of the services at public health facilities.
Keywords: Pharmacy value-added services, hospital, health clinic, refill medications, Malaysia